Grade 10 Namibian Learners' Strategies for Solving Algebraic Word Problems - Iilonga, Hesekiel Kaukolwa; Ogbonnaya, Ugorji I. (Department of Mathematics, Universitas Negeri Semarang, 2023)
Solving mathematical word problems is a big challenge for many learners. One reason for the challenge could be the use of inappropriate strategies in solving mathematical word problems. In Namibia, many examiners’ reports show that learners do not attempt algebraic word problems fairly in examinations. This study investigated Grade 10 learners’ strategies for solving algebraic word problems in the Ohangwena Region, Namibia. The study followed a qualitative approach. A sample of 351 Grade 10 learners from ten secondary schools participated in the study. Krulik and Rudnick’s problem-solving strategies model was adopted as the framework that guided the study. Data was collected using the Algebraic Word Problem Solving Achievement Test and analysed using content analysis. The result shows that most of the learners could not use appropriate strategies to solve the given problems. Few learners employed one or two appropriate strategies in solving the problems. The strategies used by the learners to solve the algebraic word problems in the test include Computing or Simplifying (CS); Making a Table, Chart, or List (TCL); Making a model or a diagram (MD), and Guessing, Checking, and Revising (GCR). It is recommended that teachers model different strategies for solving mathematical problems for learners while teaching mathematics. Keywords – problem-solving, problem-solving strategies, algebraic word problem.